METODE KELAS IBU HAMIL DALAM MENINGKATKAN PENGETAHUAN PENCEGAHAN KOMPLIKASI KEHAMILAN - Surya Atmaja, Rani Widiyanti; Lisnawati (Jurnal Kesehatan Mahardika, 2023)
The Pregnant Women Class is one of the efforts to increase mothers knowledge so that they are able to detect complications early which will contribute to reducing MMR. The pupose of this study was to compare the implementation of classes  for pregnant women in the network with face to face to increase knowledge of prevention of pregnancy complications. The research was conducted at the Majasem and Sitopeng health centers in Cirebon city. Research was with Quasy experimental methods pretest and posttest with control group. A sample of 55 pregnant women consisted of 25 case (in network) and 30 controls (face to face). The results obtained were that the majority of pregnant women were not at risk (20-35 years), namely 41 people (74,5%) with higher education (SMA, PT) as 28 people (50,9%) and not working as many as 49 people (89,1%). Pregnant multigravidas (2-4 children) were 40 people (72,5%), the majority of the Poedji score were not at risk of 40 people (72,5%) high family support was 39 people (70,9%), and the majority of prior knowledge and after class pregnant women are good. Analysis of the Chi-Square = 0.032 (<0.005) so that statistically there is a relationship between the Pregnant Women Class method and knowledge of preventing pregnancy complications.